The Legal Position Of The Will Given To The Adopted Child As Proof Of Ownership In The Gorontalo Religious Court - Meriyani Hinelo (Estudiante Law Journal, 2019)
Abstract: The purpose of this study is to find out and analyze the  Juridical Analysis of Religious Court Decision  Number: 403/PDT. G/2019/PA. Gtlo Concerning  the Determination of Probate Disputes  and the Legal Position of  the Will as proof of rights in the judgment of the Judge. Research Uses this type of normative-empirical research. Using several approaches, namely:the legal approach(statue approach),  the case approach  (case approach). The results of this study show that:  First,  that based on  juridical analysis of religious court decision  number: 403/PDT. G/2019/PA. Gtlo About  the Determination of Will Disputes has been in line with the provisions of the event law, where the first condition that must be met by the plaintiff is regarding material conditions, while the plaintiff in his lawsuit is wrong in occupying defendant 1 and defendant 2  (two). Second,  that the legal position of the Will as proof of rights in the judge's consideration is not used as a balance material by pa judges because there are   defects as intended by the researcher, therefore  the judge ruled the lawsuit is  unacceptable(Niet Onvantkelijke Verklaard)  ) which means that the case has not been completed with a positive verdict in the sense that it has not touched the subject matter and if the plaintiff wants to re-apply must complete the terms of the formil in questionKeywords: Position; Will; Dispute